2020
DOI: 10.1002/elps.201900435
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of artifact protein aggregation using tetradecyl sulfate and hexadecyl sulfate in capillary gel electrophoresis under reducing conditions

Abstract: In the biopharmaceutical industry, CE-SDS assesses the purity, heterogeneity, and stability of therapeutic proteins. However, for mAb-1 and mAb-2, typical CE-SDS under reducing conditions produced atypical protein peak profiles, which led to biased purity results, thus were not acceptable for biologics manufacturing. This bias was caused by the formation of method-induced higher molecular weight artifacts, the levels of which correlated with protein concentration. Here we show that adding sodium tetradecyl and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Replacement of SDS in SDS‐CGE separation of proteins and their peptide fragments by anionic detergents with longer alkyl chain, particularly by tetradecyl sulfate in the sample and hexadecyl sulfate in the sieving BGE, resulted in suppression of artifact protein aggregation in CGE analysis of mAbs under reducing conditions [101]. Heavy and light chains of mAbs could be separated with better repeatability and higher robustness.…”
Section: Separations By the Particular Ce And Cec Methodsmentioning
confidence: 99%
“…Replacement of SDS in SDS‐CGE separation of proteins and their peptide fragments by anionic detergents with longer alkyl chain, particularly by tetradecyl sulfate in the sample and hexadecyl sulfate in the sieving BGE, resulted in suppression of artifact protein aggregation in CGE analysis of mAbs under reducing conditions [101]. Heavy and light chains of mAbs could be separated with better repeatability and higher robustness.…”
Section: Separations By the Particular Ce And Cec Methodsmentioning
confidence: 99%
“…In view of the previous use of STS and SHS to mitigate the HC or intact mAb peak artifacts in CE-SDS [21][22][23], we tried to use CE-SHS and CE-STS to optimize the LC peak shape of mAb-A, that is, replacing the SDS of the sample and gel buffer with SHS and STS, respectively. Both CE-SHS and CE-STS have significantly optimized peak shapes (Figure 5).…”
Section: 3mentioning
confidence: 99%
“…Molina et al [20] reported HMW artifacts caused by incomplete denaturation of mAbs, and they increased the SDS concentration, denaturation temperature, and incubation time to eliminate the artifacts. Guan et al [21][22][23] also reported HMW artifacts in reducing and nonreducing modes. They attributed this phenomenon to the problem of binding between the ionic surfactant SDS and the antibody molecule.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations